EDUCATIONAL BENEFITS OF DEVELOPING SIMPLE AI CHATBOTS WITH PHP FOR STUDENTS - Ismoil Sapayev Anvar oglu; Sapayev Ismoil Anvar oglu (PEDAGOGS, 2025)
Abstract: Artificial Intelligence (AI) education increasingly emphasizes hands-on learning to help students understand theoretical concepts through practical application. Developing simple chatbots with PHP offers an accessible way for learners to explore AI principles, web development, and problem-solving. This article highlights the educational benefits of building PHP-based chatbots, including enhanced programming skills, improved understanding of conversational logic, and the integration of AI tools into everyday projects. The approach provides students with a foundation for more advanced studies while encouraging creativity and innovation.